Sustainable financing of AYSRH programs by local governments through the TCI model - Otondi, Levis; Aloo, Nancy; Kagwe, Peter; Matekwa, Assumpta; Miriti, Kenneth; Njoki, Lilly; Sama, Denis Joel; Owino, Kenneth; Nyachae, Paul (Frontiers in Global Women's Health, 2023)
Introduction Despite the existence of a legal policy framework, financing of adolescent and youth sexual and reproductive health (AYSRH) services has remained weak. External donors are the main financing agents, which has implications for the sustainability of service provision. International development partners have reduced funding for health programs from historically high levels. In Kenya, the health sector's budget allocation has remained below the 15% committed to under the Abuja declaration. With Kenya's devolved government structure, a greater proportion of financial resources are dedicated towards recurrent and structural expenses as opposed to addressing health systems gaps. Objectives The purpose of this manuscript is to assess the contribution of The Challenge Initiative (TCI) Business Unusual model on AYSRH services in the counties of Kilifi and Migori, as well as to examine the institutionalization of high impact interventions (HIIs) within the annual work plan, budget, and systems of the said counties. Additionally, this study aims to analyse the trend in contraceptive uptake among adolescent and young women aged 15 to 24 in Kilifi and Migori counties. Methods Migori and Kilifi Counties chose to partner with TCI to implement the Business Unusual model. Interested counties apply for the initiative's support and commit to contributing a portion of the funding needed to adapt and implement high impact interventions (HIIs). Based on the identified gaps, TCI supported the counties to prioritize the HIIs including integrated outreaches, youth fixed days, whole site orientation, youth champions, and youth dialogues. The program was implemented between July 2018 to June 2021 in 60 and 68 public health facilities of Kilifi and Migori Counties, respectively. The county teams identified and selected program implementation team whose key role was to coordinate, review, monitor, mobilize resources and report AYSRH program implementation progress. Results The results showed a 60% increase in financial commitments on AYSRH programming from 2018 to 2021 in both counties. The average expenditure for committed funds for Kilifi and Migori Counties was 116% and 41% respectively. As the counties continued to allocate and spend funds on the implementation of HIIs, there was a noticeable increase in contraceptive uptake among the young people aged 15 to 24 who visited health facilities for services. There was a 59% and 28% percentage increase in contraceptive uptake among young people (15–24 years) between 2018 and 2021. The proportion of adolescents amongst those presenting for first ANC clinic dropped from 29.4% in 2017 to 9% in 2021 in Kilifi County and from 32.2% in 2017 to 14% in 2021 in Migori County. Using the TCI's Sisi kwa Sisi coaching model of lead-assist-observe-monitor, 20 master coaches were trained. The master coaches cascaded the training to over 97 coaches. The coaches will continue to build capacity of peers in advocacy for resource mobilization and implementation of HIIs. At least nine of TCI's HIIs have been adopted in Kilifi and Migori County strategies and annual work plans, and there is financial support for their sustainability. Discussion The increase in adolescent contraceptive uptake might have been as a result of the system strengthening through self-financing of AYSRH programs, the institutionalization of HIIs, and the coaching. Local governments can invest in and sustain their own AYSRH programs, which will lead to an improvement in adolescent and youth access to contraceptive services and, as a result, a reduction in adolescent pregnancies, maternal mortality, and infant mortality.